2022
DOI: 10.3390/ijerph19148281
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for E-Government Adoption of SANAD App Services Integrating UTAUT, TPB, TAM, Trust, and Perceived Risk

Abstract: Using mobile applications in e-government for the purpose of health protection is a new idea during COVID-19 epidemic. Hence, the goal of this study is to examine the various factors that influence the use of SANAD App As a health protection tool. The factors were adopted from well-established models like UTAUT, TAM, and extended PBT. Using survey data from 442 SANAD App from Jordan, the model was empirically validated using AMOS 20 confirmatory factor analysis, structural equation modeling (SEM) and machine l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 69 publications
7
30
0
Order By: Relevance
“…Age, educational level, and Internet experience attributes were presented in H10, H12, and H13 and were previously used in [4,7,23,44,50,51,72,[82][83][84][85][86]. Age, educational level, and Internet experience can be attributed to behavioral intention (BI).…”
Section: Discussionmentioning
confidence: 99%
“…Age, educational level, and Internet experience attributes were presented in H10, H12, and H13 and were previously used in [4,7,23,44,50,51,72,[82][83][84][85][86]. Age, educational level, and Internet experience can be attributed to behavioral intention (BI).…”
Section: Discussionmentioning
confidence: 99%
“…This study used an extended model TAM to study the influence of parents’ anxiety and depression on children’s anxiety and depression when using SNs. The research used CFA, SEM, and five ML methods to validate and verify the findings as in [ 88 , 89 , 90 , 91 ]. The research found that there is a high correlation between parents’ depression and anxiety with children’s depression and a weak correlation with children’s anxiety.…”
Section: Discussion Implications and Conclusionmentioning
confidence: 99%
“…Anyway, different factors impact the attitude toward e-government services usage in Jordan (AlHadid et al, 2022). Quality of information, perceived ease of use, and quality of the system influence the e-government acceptance by employees of the municipality in Jordan (Shibly & Tadros, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Perceived risk, facilitating conditions, perceived service quality, performance expectancy, social influence, effort expectancy, and trust in digital technology affect attitude to e-government usage in Jordan (AlHadid et al, 2022). The key factors: facilitating conditions, perceived risk, social influence, performance expectancy, perceived service quality, effort expectancy, and trust in digital technology affect the attitude toward e-government usage in Jordan (AlHadid et al, 2022). Individual reactions such as enjoyment, habit, and local culture affect the use of e-government.…”
Section: Subjective Norms (Social Influence) and Intention To Use E-g...mentioning
confidence: 99%
See 1 more Smart Citation